Three-Point Bending Tests of Zirconia Core/Veneer Ceramics for Dental Restorations - Massimo Marrelli; Carmine Maletta; Francesco Inchingolo; Marco Alfano; Marco Tatullo (International Journal of Dentistry)
Introduction. The mechanical strength and the surface hardness of commercially available yttrium-doped zirconia were investigated. Furthermore, a comparative study of eight different ceramic veneers, to be used for the production of two-layered all-ceramic restorative systems, was carried out. Materials and Methods. Four types of zirconia specimens were analyzed, according to a standard ISO procedure (ISO 6872). Besides, two-layered zirconia-veneer specimens were prepared for three-point bending tests. Results. A strong effect of the surface roughness on the mechanical strength of zirconia specimens was observed. Finally, a comparative study of eight commercially available veneering ceramics shows different modes of failure between the selected veneers. Conclusion. The results indicate that close attention should be paid to the preparation of zirconia-based crowns and bridges by CAD/CAM process, because surface roughness has an important effect on the mechanical strength of the material. Finally, the results of the mechanical tests on two-layered specimens represent an important support to the choice of the veneering ceramic.